A Design Framework for Mathematics Learning in Junior High School to Improve Students' Mathematical Connection Ability - R, Nurmala; Usman Mulbar; Muhammad Darwis (Cita konsultindo, 2025)
This research aims to develop an innovative mathematics learning design for Junior High School students, which explicitly integrates mathematical connection skills. These connections make learning more meaningful and relevant, thus enhancing students' ability to meet the challenges of the 21st century. This design is presented as a solution to the problem of low mathematical connection skills among students and the limitations of teachers in designing effective learning experiences. This design encourages students to actively construct their own understanding of mathematical concepts and their interrelationships. This research produces a comprehensive learning design, encompassing the formulation of measurable learning outcomes, the mapping and organization of coherent learning materials, and the design of learning activities and assessment strategies that align with the goal of developing mathematical connection skills. After undergoing a validation process by two expert reviewers, achieving an average score of 3.40 and categorized as valid, and incorporating minor revisions based on their feedback, this mathematics learning design is deemed ready to be piloted in learning setting. However, the scope of this article is limited to the development and validation stages of the learning design. This research is expected to make a significant contribution to improving the quality of mathematics learning at the Junior High School level, as well as equipping students with the critical thinking, creative, and problem-solving skills essential for their future success. By equipping students with strong mathematical connection skills, they will possess the essential thinking skills for success in the future, both in academic and non-academic fields.